Implementasi Plugin YOAST SEO Website Informasi Berbasis Wordpress (Studi Kasus: KCP MNC Bank Puri Indah) - Ruly Suryana; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
There are so many forms of information through websites that are interesting in writing and appearance so that the information spreads quickly and widely among the public. But there are still many blog or website writers who don't know how to write the right articles. In writing an article, you must pay attention to writing rules such as title tags, meta description tags, backlinks, meta keyword tags, keyword density, permalinks, outbound links, internal links, keyphrases, meta descriptions, and others. There needs to be an interesting article writing strategy so that it can be easily indexed by Google Search Robots and easy to find on the Search Engine Result Page ( SERP ). For that we need a touch of search engine optimization techniques or search engine optimization ( SEO ). With the YOAST SEO plugin in CMS Wordpress, it makes articles quality so Goggle will recommend everyone to type these keywords. YOAST SEO will analyze directly whether the words and sentences in the article are in accordance with SEO techniques or not. This research discusses SEO ( Search Engine Optimization ) with Wordpress CMS and selects the configuration of supporting tools such as hosting and domains, templates, Elementor plugins, then monitors website ranking using Wincher and Google Search Console which will affect the position of the article on SERP ( Search ). Engine Result Page ) Google.